A Systematic Analysis of the Impact of an Ambulatory Ophthalmology Urgent Care Clinic - Sally S.E. Park; Rohin Vij; Jeff Wu; Bryan Zarrin; Jee-Young Moon; Jason Oliveira; Jeffrey S. Schultz; Anurag Shrivastava (Journal of Academic Ophthalmology, 2022)
Importance A same-day ophthalmic urgent care clinic can provide efficient eye care, a rich educational environment, and can improve patient experience. Objective The aim of this study was to systematically evaluate volume, financial impact, care metrics, and the breadth of pathology of urgent new patient encounters based on their site of initial presentation. Design, Setting, and Participants A retrospective analysis was performed on consecutive urgent new patient evaluations in our same-day triage clinic at the Henkind Eye Institute at Montefiore Medical Center between February 2019 and January 2020. The cohort of patients who presented directly to this urgent care clinic were referred to as the “TRIAGE” group. Patients who initially presented to an emergency department (ED), and were subsequently referred to our triage clinic, are referred to as the “ED + TRIAGE” group. Main Outcomes and Measures Visits were evaluated on a variety of metrics, including diagnosis, duration, charge, cost, and revenue. Furthermore, return to the ED or inpatient admission was documented. Results Of 3,482 visits analyzed, 2,538 (72.9%) were in the “TRIAGE” group. Common presenting diagnoses were ocular surface disease (n = 486, 19.1%), trauma (n = 342, 13.5%; most commonly surface abrasion n = 195, 7.7%), and infectious conjunctivitis (n = 304, 12.0%). Patients in the “TRIAGE” group, on average, were seen 184.6% faster (158.2 vs. 450.2 minutes) than patients in the “ED + TRIAGE” group (p < 0.001). The “ED + TRIAGE” group were furthermore found to generate 442.1% higher charges ($870.20 vs. 4717.70) and were associated with 175.1% higher cost ($908.80 vs. 330.40) per patient. The hospital was found to save money when noncommercially insured patients with ophthalmic complaints presented to the triage clinic instead of the ED. Patients seen in the triage clinic had a low rate of readmission to the ED (n = 42, 1.2%). Conclusions and Relevance A same-day ophthalmology triage clinic provides efficient care, while providing a rich learning environment for residents. Less wait time with direct access to subspecialist care can help improve quality, outcome, and satisfaction metrics.